Home energy monitoring software system (HEMS) - mobile application and web-based dashboard - Wong, Ke Xin (2024)
The increasing energy demand driven by economic expansion, population growth, and urbanization in Malaysia poses environmental challenges due to the heavy reliance on non-renewable fossil fuels to generate electricity, which contributes to greenhouse gas emissions and global warming. The proposed Home Energy Monitoring System (HEMS) leveraging IoT technology has been developed to address these challenges by empowering residents to actively monitor, analyze, and optimize their electricity consumption through mobile applications to foster sustainable energy practices and mitigate carbon emissions in Malaysia. The project aims to determine project requirements, develop a mobile application for monitoring residential energy usage, create a web-based dashboard for visualizing energy consumption data, and evaluate functionalities through various tests. The target user for the mobile application is the residents in Malaysia who have home energy monitoring devices installed in their residences, and the target user for the web-based dashboard is an administrator who manages the accounts for residents. The functionalities of both mobile applications and web-based dashboards, such as monitoring real-time energy consumption, viewing historical energy consumption, setting thresholds to manage energy consumption, managing user profiles and viewing resident dashboards, are successfully developed using iterative and incremental development methodologies to develop different functionalities in phases. Testing such as unit testing, integration testing, system testing, code quality analysis and system usability scale evaluation were conducted throughout development to ensure a smooth user experience. The system has achieved As in maintainability, reliability, security and usability indicating its suitability for routine operations. Through collaboration with MIMOS Berhad, the goal and objectives of the project have been achieved successfully within the timeline, with the mobile application and web-based dashboard prototype as the final deliverables.